Ответ(ы) на вопрос:
[latex](13 \frac{1}{6}-2 \frac{2}{13} *2 \frac{10}{21})*1 \frac{5}{47}[/latex]
[latex]1) 2 \frac{2}{13} *2 \frac{10}{21}= \frac{28}{13}* \frac{52}{21} = \frac{208}{39} [/latex]
[latex]2) 13 \frac{1}{6} - \frac{208}{39}= \frac{79}{6}- \frac{208}{39}= \frac{ 79^{13}- 208^{2} }{78} = \frac{1027-416}{78} = \frac{611}{78} [/latex]
[latex]3) \frac{611}{78}*1 \frac{5}{47}= \frac{611}{78}* \frac{52}{47} = \frac{13*26}{39*1}= \frac{338}{39}=8 \frac{26}{39} [/latex]
Не нашли ответ?
Похожие вопросы